2016
DOI: 10.2215/cjn.05760516
|View full text |Cite
|
Sign up to set email alerts
|

Serious Illness Conversations in ESRD

Abstract: Dialysis-dependent ESRD is a serious illness with high disease burden, morbidity, and mortality. Mortality in the first year on dialysis for individuals over age 75 years old approaches 40%, and even those with better prognoses face multiple hospitalizations and declining functional status. In the last month of life, patients on dialysis over age 65 years old experience higher rates of hospitalization, intensive care unit admission, procedures, and death in hospital than patients with cancer or heart failure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 47 publications
(67 reference statements)
2
87
0
1
Order By: Relevance
“…Moreover, the effect of functional loss is highly dependent on personal values and patient preferences. Thus, it is important to use the predialysis phase to explore an individual's health goals (e.g., living at home, engage in social activities) and current quality of life (46). This could improve shared decision making regarding dialysis and conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect of functional loss is highly dependent on personal values and patient preferences. Thus, it is important to use the predialysis phase to explore an individual's health goals (e.g., living at home, engage in social activities) and current quality of life (46). This could improve shared decision making regarding dialysis and conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…Ho and colleagues found that physicians felt uncomfortable with death and dying and perceived that other professionals were better trained to conduct these conversations. This is in line with a recent study involving dialysis care physicians . Reasons for hesitation were that they felt uncertain about their skills to handle the conversations.…”
Section: Discussionmentioning
confidence: 99%
“…Though a kidney transplant is an effective solution, donor supply is well short of demand and transplant is not an option for many (Crews et al, 2019). End-stage renal disease is treated with dialysis, but dialysis is associated with high rates of morbidity and mortality (Mandel et al, 2016). Synthetic approaches to generate new kidney structures require a detailed understanding of kidney cell types and their actions (Oxburgh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%